Anisotropic Optical and Mechanical Properties in Few‐Layer GaPS4. Issue 8 (12th February 2023) - Liu, Shuai; Cui, Xuwei; Zhang, Qinghua; Shen, Wanfu; Du, JianTao; Lin, Ting; Wang, Yunkun; Wu, Minghui; Gu, Lin; Gao, Yunan; Hu, Chunguang; Liu, Luqi; et al.
Abstract: Low‐symmetry 2D materials have received tremendous attention due to their anisotropic optical, electrical, and mechanical properties and viable candidates for polarized photodetectors, anisotropic field‐effect transistors, and nanomechanical systems. Here, an interesting low‐symmetry 2D material (GaPS4 ) is reported and its in‐plane anisotropic structure, optical, and mechanical properties are investigated. The polarized Raman and absorption spectra prove the sensitivity of GaPS4 to crystalline orientation and linear dichroism. The experimental results of azimuth‐dependent reflectance difference microscopy can visually reveal the in‐plane optical anisotropy of GaPS4 flakes. Moreover, an interesting pressurized bubble method is designed to verify the anisotropic mechanical properties of GaPS4 flakes and saddle‐like bubble devices of GaPS4 are successfully fabricated. The saddle‐like bubble devices exhibit visual anisotropic deflection variations along the orthogonal direction. Kelvin probe force microscope enables the direct identifying of the surface potential distribution of bubble devices under strain. Interest would be excited in the anisotropic optical and mechanical properties and relevant device applications of low‐symmetry 2D materials. Abstract : In‐plane optical anisotropy of GaPS4 flakes is thoroughly studied through polarized Raman, azimuth‐dependent reflectance difference microscopy, and polarized absorption spectra measurements. A pressurized bubble method is proposed to visually verify the anisotropic mechanical properties of GaPS4 flakes. Under the action of isotropic pressures, the bubble devices of GaPS4 exhibit anisotropic deflection changes.